Digital divide: an inquiry on the native communities of Sabah - Fang, Yi Xue; Gill, Sarjit S.; Kunasekaran, Puvaneswaran; Rosnon, Mohd Roslan; Talib, Ahmad Tarmizi; Abd Aziz, Azureen (MDPI, 2022)
ICT development has become the development pulse of the global nation. Malaysia, as a developing nation, has invested heavily in ICT development across the country to ensure no one is left behind. The policymakers have also claimed a positive result in closing the digital gap among their people. In this study, Van Dijk’s theory of digital divide is explored on the four dimensions of digital divide (motivation, physical, skill, and usage) among the native people in Sabah. A focus group discussion (FGD) was conducted among 21 key informants from seven different ethnic groups to identify the issues of ICT development in their community. The findings showed that the existence of a digital gap between the rural and the urban area community caused the community to be saddled with the connection to telecommunication service, including landline and internet. Despite lacking, the native community were receptive and willing to adopt the ICT positively for their daily activities. While the theory of digital divide observes that the physical access divide is narrowing in most developed nations, this study shows that is not the case for developing countries, such as Malaysia. The inequality in digital access is prevalent among the natives in Sabah, which could result in the opportunity to participate in important democratic decision-making.